2019
DOI: 10.1002/jcp.28779
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs associated with multiple sclerosis expressed in the Th1 cell lineage

Abstract: Multiple sclerosis (MS) is a type of inflammatory and demyelinating disorder of the central nervous system in which immune-mediated inflammatory processes are elicited by secreted cytokines from T helper (Th)-1 and Th17 cells. While some protein-coding genes expressed in T cell types have established involvement in MS disease progression, little is understood about the roles of long noncoding RNAs (lncRNAs) within the disease landscape. LncRNAs, noncoding RNAs longer than 200 nucleotides, likely control gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 39 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Among the included studies, 47 studies were conducted on human samples ( 24 70 ), 7 studies used animal models ( 45 , 71 76 ), and only 1 research was conducted on both human samples and animal model ( 45 ). Also, 33 studies were conducted in the Iranian population ( 24 26 , 28 34 , 36 , 38 – 43 , 45 55 , 57 , 58 , 61 , 66 , 67 ), 9 studies were in China ( 68 76 ), 5 studies were in Egypt ( 37 , 62 65 ), 4 studies were in Italy ( 27 , 35 , 59 , 60 ), 1 study was in Russia ( 44 ), and 1 study was in the Netherlands ( 56 ). A total of 44 studies evaluated the expression of lncRNAs in MS patients ( 24 , 26 31 , 34 43 , 45 , 46 , 48 , 50 54 , 56 61 , 63 65 , 67 76 ), while 9 other studies analyzed polymorphisms of lncRNAs ( 25 , 32 , 33 , 44 , 47 , 49 , 55 , 62 , 66 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included studies, 47 studies were conducted on human samples ( 24 70 ), 7 studies used animal models ( 45 , 71 76 ), and only 1 research was conducted on both human samples and animal model ( 45 ). Also, 33 studies were conducted in the Iranian population ( 24 26 , 28 34 , 36 , 38 – 43 , 45 55 , 57 , 58 , 61 , 66 , 67 ), 9 studies were in China ( 68 76 ), 5 studies were in Egypt ( 37 , 62 65 ), 4 studies were in Italy ( 27 , 35 , 59 , 60 ), 1 study was in Russia ( 44 ), and 1 study was in the Netherlands ( 56 ). A total of 44 studies evaluated the expression of lncRNAs in MS patients ( 24 , 26 31 , 34 43 , 45 , 46 , 48 , 50 54 , 56 61 , 63 65 , 67 76 ), while 9 other studies analyzed polymorphisms of lncRNAs ( 25 , 32 , 33 , 44 , 47 , 49 , 55 , 62 , 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…AC007278.2 has a specific expression in Th1 cells. It is located within the introns of the protein-coding genes IL18RAP and IL18R1 , with important roles in Th1 cell differentiation ( 43 ). Several studies revealed significant correlations between IL18RAP and IL18R1 and their association with the lncRNA AC007278.2.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, no reports about AC005392.3 have been recorded. The expression level of AC007278.2 is upregulated in peripheral blood mononuclear cells in multiple sclerosis (22). The IL-18 cytokine, coded by interleukin 18 receptor 1 (IL18R1), has been found to be involved in atherosclerosis and cardiovascular complications (23).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs encoded by the gene AC007278.2 and IFNG antisense RNA 1 (IFNG-AS1-001) showed significantly higher expression in the relapsing MS phase whereas IFNG-AS1-003 was elevated in patients in the remitting MS phase compared with relapsing patients. Together, these deregulated lncRNAs may provide valuable tools for understanding the relationships between lncRNAs and MS progression as well as new pathological pathways [ 50 ]. Little is known about the precise roles of these lncRNAs but based on the expression profiles, lncRNAs appear to be important in the regulation of immune functions and are of potential biological significance for MS pathogenesis [ 122 ].…”
Section: Role Of Ncrnas In Multiple Sclerosismentioning
confidence: 99%